2021
DOI: 10.1002/pon.5644
|View full text |Cite
|
Sign up to set email alerts
|

The multiple mediating effects of cancer threat appraisal and quality of life on the association between mindfulness and depression for colorectal cancer survivors

Abstract: Objective This study explored the multiple mediating effects of cancer threat appraisal, functional status, and symptom distress on the association between mindfulness and depression in colorectal cancer (CRC) patients at the transition stage after completing cancer treatments. Methods A total of 90 CRC survivors who received cancer treatments within 3 months participated in this cross‐sectional study. The functional status and symptom distress (EORTC‐C30 and EORTC CR29), dispositional mindfulness (Five Facet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Results suggest that less mindful cancer patients reported more negative affect, through greater stress appraisal and more use of rumination. This results is in line with previous studies showing that more mindful cancer patients may experience less negative affect, as they are less likely to perceive events as stressful and threatening (i.e., lower stress appraisal) 23 and are less likely to ruminate 37 . Additionally, Mindfulness‐to‐Meaning Theory suggests that the decentering aspect of mindfulness hinders perseverative cognition, such as rumination, by facilitating the release or “letting go” of negative thoughts and emotions, which in turns, alleviates psychological distress 32 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Results suggest that less mindful cancer patients reported more negative affect, through greater stress appraisal and more use of rumination. This results is in line with previous studies showing that more mindful cancer patients may experience less negative affect, as they are less likely to perceive events as stressful and threatening (i.e., lower stress appraisal) 23 and are less likely to ruminate 37 . Additionally, Mindfulness‐to‐Meaning Theory suggests that the decentering aspect of mindfulness hinders perseverative cognition, such as rumination, by facilitating the release or “letting go” of negative thoughts and emotions, which in turns, alleviates psychological distress 32 .…”
Section: Discussionsupporting
confidence: 93%
“…For example, a cross-sectional study in colorectal cancer patients found that mindfulness was related to lower threat appraisal of cancer, subsequently related to less depressive symptoms. 23 To the best of our knowledge, this is the first study in cancer patients that aims to examine the role of both stress appraisal and several adaptive and maladaptive coping strategies as mechanisms in the relationship between mindfulness and affect. As differential relationships have been found between mindfulness and positive and negative affect, 24 separate analyses were conducted for positive and negative affect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of regional hospitalizations to identify the prevalence of clinically significant anxiety as well as other mental disorders might lead to underestimates, because estimated prevalence is generally higher when questionnaires are used [63,64]. Considering the well-known underestimated prevalence of mental disorders, especially in low-and middle-income countries [65], and their negative effects on quality of life, scanning for symptoms of anxiety and depression, implementation of dietary and physical activity interventions, and implementation of social support are of utmost importance among CRC patients at diagnosis and even years after treatment [66][67][68].…”
Section: Principal Findingsmentioning
confidence: 99%